An integrated framework of community resilience to earthquakes: Implications for disaster risk reduction and recovery engineering - Abraham Louis Pandu; Al Fitrah Asril; Mohammad Akbar Ogy Darmawan (Calamity: A Journal of Disaster Technology and Engineering, 2026)
Background: Indonesia is prone to earthquakes because it is located at the meeting point of tectonic plates, resulting in many coastal areas having a high risk of disaster. Earthquakes not only cause physical damage but also have a long-term impact on the psychological and social conditions of the community. Therefore, community resilience is an important factor in reducing disaster risk and supporting the post-disaster recovery process. This study aims to examine the concept of community resilience in facing earthquakes and the factors that influence it. Methods: This scientific paper uses a literature review method by examining accredited scientific journals, disaster textbooks, official agency reports, and relevant laws and regulations. Findings: The results of the study show that community resilience to earthquakes is shaped by the integration of social, economic, physical and infrastructure aspects, human resources, and the environment. Social aspects and social capital play an important role in accelerating post-disaster response and recovery, while economic capacity and infrastructure quality determine the community's ability to absorb the impact of disasters. These findings are in line with resilience theory, which emphasizes adaptive capacity and collective engagement as key factors in community resilience. Conclusion: Community resilience to earthquakes is built through the integration of social, economic, physical, human resource, and environmental aspects that reinforce each other. Strengthening the adaptive capacity of communities in an integrated manner is key to reducing the impact of disasters and supporting post-disaster recovery and sustainability. Novelty/Originality of this article: The novelty of this research lies in its comprehensive conceptual synthesis of community resilience to earthquake disasters by integrating social, economic, physical, human resource, and ecological perspectives into a single framework of discussion.